2018
DOI: 10.3168/jds.2017-13367
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a commercial vacuum fly trap for controlling flies on organic dairy farms

Abstract: The objective of this study was to evaluate the efficacy of a commercial vacuum fly trap (CowVac, Spalding Laboratories, Reno, NV) in on-farm organic dairy production systems to control horn flies, stable flies, and face flies. As cows walk through the trap, flies are brushed off the face, flank, and back with hanging flaps and blown off the belly, udder, and legs from one side, and then vacuumed from the air into a chamber from vacuum inlets opposite the blower and above the cow. The study included 8 organic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 26 publications
(35 reference statements)
1
14
0
Order By: Relevance
“…In grazing herds, few to no studies have evaluated increases in activity; however, the low correlations in Sjostrom et al (2016) demonstrated a trend ( P = 0.10) for higher activity due to stable flies and fly avoidance behaviors. Kienitz et al (2018) reported that flies on cows may be challenging for organic dairy farms, and that farms similar to the experimental herd in the current study, would benefit from fly control methods to improve milk production and animal welfare.…”
Section: Resultsmentioning
confidence: 79%
“…In grazing herds, few to no studies have evaluated increases in activity; however, the low correlations in Sjostrom et al (2016) demonstrated a trend ( P = 0.10) for higher activity due to stable flies and fly avoidance behaviors. Kienitz et al (2018) reported that flies on cows may be challenging for organic dairy farms, and that farms similar to the experimental herd in the current study, would benefit from fly control methods to improve milk production and animal welfare.…”
Section: Resultsmentioning
confidence: 79%
“…Stable flies on front and back legs were recorded as the mean number of stable flies per leg, horn flies per a cow's side, and face flies per a cow's face. Fly counts were made from a distance of 4 m (Kienitz et al, 2018;Perttu et al, 2020). Ten behavior observations were conducted twice per day on every cow: once in the morning and once in the afternoon.…”
Section: Behavioral and Biological Measurementsmentioning
confidence: 99%
“…At certain parameters, EMFs are widely used to enable suppressing action on insects [11]. Paper [11] shows that the cells of insects are able to absorb the electromagnetic energy from a millimeter range of wavelengths. All changes that are significant for larvae start and finish at the cellular level.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…Expressions (11) to (13) allow us to derive from (9) the electric and magnetic components of the internal field for the first approximation. In this case, one can see that the main difficulty in determining the internal fields is associated with the calculation of elliptic integrals.…”
Section: Theoretical Analysis Of the Interaction Of Electromagnetic Fmentioning
confidence: 99%
See 1 more Smart Citation